2001
DOI: 10.1161/hc3801.095663
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated Heme Oxygenase-1 Gene Transfer Inhibits the Development of Atherosclerosis in Apolipoprotein E–Deficient Mice

Abstract: Background-Increasing evidence supports the role of heme oxygenase-1 (HO-1) in cytoprotective response and iron homeostasis. The object of this study was to investigate whether adenovirus-mediated gene transfer of HO-1 in arteries reduces iron overload and inhibits lesion formation in apolipoprotein E (apoE)-deficient mice. Methods and Results-Infection of rat aortic smooth muscle cells with adenovirus carrying the human HO-1 gene (Adv-HO-1) resulted in a high-level expression of HO-1 protein, which effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
204
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(212 citation statements)
references
References 29 publications
(32 reference statements)
8
204
0
Order By: Relevance
“…Induction of HO-1 by chemical inducers results in the reduction of atherosclerotic lesions in LDL-receptor knockout mice and prevents transplant arteriosclerosis in mouse cardiac allografts (Hancock et al, 1998;Ishikawa et al, 2001). Similarly, adenovirus-mediated transfer of HO-1 to arteries significantly attenuates the development of atherosclerosis in apoE null mice and graft arteriosclerosis in a rat model of chronic allogeneic aorta rejection (Juan et al, 2001;Bouche et al, 2002). In addition, upregulation of HO-1 by heme analogues or by retroviral gene delivery lowers blood pressure in spontaneously hypertensive rats (Levere et al, 1990;Johnson et al, 1995;Sabaawy et al, 2001) while the targeted overexpression of HO-1 in lungs protects against pulmonary vessel wall hypertrophy induced by hypoxia (Minamino et al, 2001).…”
Section: Ho-1 As a Therapeutic Target In Vascular Diseasementioning
confidence: 98%
“…Induction of HO-1 by chemical inducers results in the reduction of atherosclerotic lesions in LDL-receptor knockout mice and prevents transplant arteriosclerosis in mouse cardiac allografts (Hancock et al, 1998;Ishikawa et al, 2001). Similarly, adenovirus-mediated transfer of HO-1 to arteries significantly attenuates the development of atherosclerosis in apoE null mice and graft arteriosclerosis in a rat model of chronic allogeneic aorta rejection (Juan et al, 2001;Bouche et al, 2002). In addition, upregulation of HO-1 by heme analogues or by retroviral gene delivery lowers blood pressure in spontaneously hypertensive rats (Levere et al, 1990;Johnson et al, 1995;Sabaawy et al, 2001) while the targeted overexpression of HO-1 in lungs protects against pulmonary vessel wall hypertrophy induced by hypoxia (Minamino et al, 2001).…”
Section: Ho-1 As a Therapeutic Target In Vascular Diseasementioning
confidence: 98%
“…Recombinant adenovirus containing human HO-1 (Adv-HO-1) gene was prepared as described previously [4].…”
Section: Preparation Of Recombinant Adenovirusmentioning
confidence: 99%
“…Fifty lg of proteins was electrophoresed on 10% SDS-polyacrylamide gel and the transblotted onto the Immobilon TM -P membrane (Millipore). Western blot analysis was carried out as describe previously [4].…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the progress of atherosclerosis, under certain circumstances when some of the critical antioxidant enzymes including glutathione and superoxide dismutase (SOD) were reduced and the production of NO in endothelial cells was diminished, the activation of HO/CO pathway will build up an alternative important defense against oxidative insult. Recently, Juan et al [34] reported that adenovirus-mediated HO-1 gene transfer could inhibit the development of atherosclerosis in apoE-deficient mice. We here found that the over-expression of hHO-1 in the transfected VSMC could directly and significantly inhibit VSMC proliferation.…”
Section: Increase Of Cellular Cgmp and Decrease Of Mapk Phosphorylationmentioning
confidence: 99%